2017
DOI: 10.2460/ajvr.78.9.1085
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic findings in dogs with head trauma and development of a novel prognostic computed tomography–based scoring system

Abstract: OBJECTIVE To characterize CT findings and outcomes in dogs with head trauma and design a prognostic scale. ANIMALS 27 dogs admitted to the Koret School Veterinary Teaching Hospital within 72 hours after traumatic head injury that underwent CT imaging of the head. PROCEDURES Data were extracted from medical records regarding dog signalment, history, physical and neurologic examination findings, and modified Glasgow coma scale scores. All CT images were retrospectively evaluated by a radiologist unaware of dog s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 24 publications
(33 reference statements)
3
16
1
Order By: Relevance
“…Early CT of canine TBI patients proved to be a valuable tool in the detection of structural abnormalities including midline shift, brain herniation, and skull fractures. The majority of cases (87.5%) had abnormalities detected; this is consistent with previous studies 10–12 . Skull fractures were the most commonly identified imaging feature and of those cases, 72.4% involved the neurocranium.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Early CT of canine TBI patients proved to be a valuable tool in the detection of structural abnormalities including midline shift, brain herniation, and skull fractures. The majority of cases (87.5%) had abnormalities detected; this is consistent with previous studies 10–12 . Skull fractures were the most commonly identified imaging feature and of those cases, 72.4% involved the neurocranium.…”
Section: Discussionsupporting
confidence: 89%
“…Availability of post contrast images was not an inclusion criterion. A time frame of up to 72 h posttrauma was chosen for consistency with other studies 11 . Dogs that died during the course of treatment where death was obviously unrelated to TBI, or where medical records or imaging studies were incomplete or unavailable for review, were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the incidence rate of ventricular dilation occurring after a severe traumatic head injury is known to be about 39–44%, and increased ventricular size was found to be evident 4 weeks after sustaining an injury [23]. One report showed that the prevalence of hydrocephalus among dogs with head trauma was 26% (7/27), which was concluded to be an incidental finding [24]. There is no report on acquired hydrocephalus following the development of GBI in both humans and dogs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, other intracranial changes such as brain edema or intra-axial or extra-axial hemorrhage were almost exclusively found in patients with this region affected. Previous studies have reported several aspects of TBI both on MRI and CT. 8,23 The main aim of these studies was to develop prognostic scores for dogs after suffering head trauma with brain involvement. In both studies, significant associations were found between MRI and CT findings and prognosis in dogs with TBI.…”
Section: Discussionmentioning
confidence: 99%